The role of DNA methyltransferase activity in cocaine treatment and withdrawal in the nucleus accumbens of mice. (7th February 2019) - Urb, Mari; Niinep, Kerly; Matsalu, Terje; Kipper, Karin; Herodes, Koit; Zharkovsky, Alexander; Timmusk, Tõnis; Anier, Kaili; Kalda, Anti
Abstract: An increasing number of reports have provided crucial evidence that epigenetic modifications, such as DNA methylation, may be involved in initiating and establishing psychostimulant‐induced stable changes at the cellular level by coordinating the expression of gene networks, which then manifests as long‐term behavioral changes. In this study, we evaluated the enzyme activity of DNA methyltransferases (DNMTs) after cocaine treatment and during withdrawal. Furthermore, we studied how genetic or pharmacological inhibition of DNMTs in mouse nucleus accumbens (NAc) affects the induction and expression of cocaine‐induced behavioral sensitization. Our results showed that after silencing Dnmt3a in the NAc during the induction phase of cocaine‐induced sensitization, overall DNMT activity decreases, correlating negatively with behavioral sensitization. Reduced Dnmt3a mRNA during this phase was the largest contributing factor for decreased DNMT activity. Cocaine withdrawal and a challenge dose increased DNMT activity in the NAc, which was associated with the expression of behavioral sensitization. Long‐term selective Dnmt3a transcription silencing in the NAc did not alter DNMT activity or the expression of cocaine‐induced behavioral sensitization. However, bilateral intra‐NAc injection of a non‐specific inhibitor of DNMT (RG108) during withdrawal from cocaine decreased DNMT activity in the NAc and had a small effect on the expression of cocaine‐induced behavioral sensitization. Thus, cocaine treatment and withdrawal is associated with biphasic changes in DNMT activity in the NAc, and the expression of behavioral sensitization decreases with non‐selective inhibition of DNMT but not with selective silencing of Dnmt3a . Abstract : Our data suggest that during the induction phase of cocaine‐induced behavioral sensitization, DNA methyltransferase (DNMT) activity decreases and is negatively correlated with behavioral sensitization. These results suggest importance of DNMT activity during the cocaine treatment and withdrawal.